Investigating the Use of Density Polyethylene in Modifying Bitumen to Improve Performance of Flexible Pavements Along Climbing Lanes - Marvin Ainebyona (Uganda Christian University, 2024)
This research project investigates the use of linear low density polyethylene (LLDPE) as a modifier for bitumen in flexible pavements along climbing lanes. The LLDPE was incorporated into the bitumen in granular form at a mixing temperature of 150oC until achieving homogeneity. Key experiments conducted on the modified bitumen encompassed penetration, softening point, ductility tests, and the determination of temperature susceptibility via Penetration Index assessment. Upon modification with 2% LLDPE, the penetration value transitioned from 60/70 to 40/50. The softening point had a 7% rise, while ductility had a reduction of 30%. These results implied an improved stiffness in the bitumen. The Penetration Index demonstrated a substantial 60% decrease, indicating enhanced temperature stability of the bitumen. Subsequently, an asphalt mixture (asphalt cores) was prepared while utilizing the modified bitumen. Results indicated a 12% increase in air voids value, a 17% increase in stability, and a 5% reduction in flow. Additionally, there was a 1% rise in the TSR (Tensile Strength Ratio) value, signifying improved tensile strength characteristics. These findings suggest that incorporating LLDPE as a bitumen modifier yields positive alterations in the properties of asphalt mixtures, potentially enhancing their performance and durability of flexible pavements along climbing lanes.